2014
DOI: 10.3109/1547691x.2014.938874
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous anesthetic propofol suppresses prostaglandin E2and cysteinyl leukotriene production and reduces edema formation in arachidonic acid-induced ear inflammation

Abstract: Propofol is an intravenous drug widely used for anesthesia and sedation. Previously, propofol was shown to inhibit cyclo-oxygenase (COX) and 5-lipoxygenase (5-LOX) activities. Because these enzyme-inhibiting effects have only been demonstrated in vitro, this study sought to ascertain whether similar effects might also be observed in vivo. In the current studies, effects of propofol were tested in a murine model of arachidonic acid-induced ear inflammation. Specifically, propofol -as a pre-treatment -was intrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…We demonstrated that lesser amounts of LTB 4 , 5‐HETE, 5‐HpETE, 5S,6S‐DiHETE, 5S,6R‐DiHETE, and all‐trans‐LTB 4 were produced in the presence of propofol. The effect of propofol on LTB 4 was reported by Inada et al (3638), and our result is compatible with theirs. 5S,6S‐DiHETE, 5S,6R‐DiHETE, and all‐trans‐LTB 4 are products of LTA 4 , which is produced via 5‐LOX.…”
Section: Discussionsupporting
confidence: 94%
“…We demonstrated that lesser amounts of LTB 4 , 5‐HETE, 5‐HpETE, 5S,6S‐DiHETE, 5S,6R‐DiHETE, and all‐trans‐LTB 4 were produced in the presence of propofol. The effect of propofol on LTB 4 was reported by Inada et al (3638), and our result is compatible with theirs. 5S,6S‐DiHETE, 5S,6R‐DiHETE, and all‐trans‐LTB 4 are products of LTA 4 , which is produced via 5‐LOX.…”
Section: Discussionsupporting
confidence: 94%
“…Propofol is known to have brochodilatating properties 36,37 , be anticonvulsive 38 and decrease intracerebral bloodflow and intracranial pressure 39,40 . Propofol possesses anti-inflammatory activity 41 and have shown antioxidative effects 42,43 . It also has antiemetic properties 6 17 .…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%
“…A study on mice showed that sevoflurane promotes PG E2 production in peritoneal macrophages [13]. Other studies have reported that propofol improves ear edema formation and reduces PGE2 production [14], inhibiting cyclooxygenase activity, and suppressing PG E2 production from dendritic cells [15]. Considering PG E2 regulates fertilization and protects the sperm against phagocytosis in the ovary [16], propofol came to the forefront in our study about PGE2.…”
Section: Discussionmentioning
confidence: 86%